Principles and methodological approaches to efficient use of land - Ovchinnikova Natalia; Aliyeva Natalia; Petrova Irina (E3S Web of Conferences, 2021)
The use of commercial land, land parcels or land in general refers to an objectively complex process being one of the main components of land relations revealing their content. The principle of rational land use acquires its objective character on a basis of clear interaction between technical, technological, natural-biological, socio-economic and environmental components that ensure effectiveness of law of continuous recovery of soil fertility and productivity of agricultural lands. Land use is a process providing implementation of these properties which manifests itself as growth of production.